Alfabetiza????o cient??fica na educa????o infantil - Cardoso, Marcia Aparecida Guimar??es (2020)
This dissertation has as its object the teaching perceptions and representations regarding the impacts of Scientific Literacy on Early Childhood Education and on sustainable behavior in children. It understands that Scientific Literacy in Early Childhood Education is a process by which the children begins to appropriate scientific knowledge and manages to make connections between that knowledge and the world around them, so that their cognitive abilities to observe, question, investigate, to argue, to explore and to interpret phenomena of their reality are amplified and are developed. Their search for solutions to the problems of their daily lives and the observation of environmental degradation is enhanced through scientific experiments, concrete and playful pedagogical activities, which will enable them to understand the world in its different dimensions: human, social and cultural. Sustainability is seen as the coexistence relationship that people create with other living beings on the planet, in a dynamic process, transforming the natural environments where they live, without causing environmental degradation or the depletion of natural resources, with a view to survival too future generations. This research seeks to verify if the pedagogical practices of teachers, in Early Childhood Education, involving Scientific Literacy, develop according to the teachers??? opinion, a more sustainable or less sustainable behavior in children. Methodologically, it is a qualitative research, whose instruments of data collection consisted of: (i) instrument for collecting the trend of opinion of teachers, based on the Likert Scale, and (ii) semi-structured in-depth interviews. Both were applied to teachers who work with children aged four and five years old from two early childhood schools in the city of S??o Paulo. The theoretical contribution was based on the approach of Scientific Literacy and sustainability, discussed by Lucia Helena Sasseron, Attico Chassot, Moacir Gadotti, Francisco Guti??rrez, Paulo Freire, Em??lia Ferreiro, Zilma Ramos de Oliveira, with emphasis on the categories literacy, experimentation, children, sustainability and awareness. Final considerations about teaching perceptions and representations reveal that scientifically literate children in early childhood education, when they come into contact with environmental issues, develop more sustainable behavior. Pedagogical proposals that involve concrete and playful experiments awaken, in children, a posture aimed at the preservation of natural resources, care for the Earth and harmonious coexistence with other living beings. In short, they express, in the opinion of the teachers of the research that resulted in this dissertation, more awareness and responsibility for the preservation of the world, reflecting responsibility for the future of the planet and the new generations.